Interference with the spatial organization of Ras in cancer cells - Truxius, Dina Carolin (Technische Universität Dortmund, 2015)
Oncogenic KRas is associated with a multitude of human cancers, like pancreatic, colorectal, and lung carcinomas, concomitant with poor prognosis and survival. Oncogenic mutations retain Ras in a constitutively active conformation, causing sustained activation of downstream signaling cascades, which leads to uncontrolled proliferation and survival. Hence, all Ras proteins are interesting molecules for targeted cancer therapies. Although the structure and functions of Ras proteins are known, it still remains an “undruggable” protein so far. In this work, the cancer phenotype upon RNAi and pharmacological inhibition in several KRas addiction model systems was elaborated. First, in a panel of hu-man cancer cell lines, from various tumor origins, the interference with the cancer phenotype after PDEδ inhibitor treatment and inducible shRNA-mediated downmodulation of PDEδ was studied. These cell lines exhibited different degrees of oncogenic KRas dependencies and a strong effect on cell survival could only be observed in KRas-dependent pancreatic and lung tumor cells, whereas colorectal carcinoma cells with an oncogenic KRas background were only slightly affected. Cells with wildtype KRas remained mostly unaffected. The new class PDEδ inhibitor Deltazinone 1 and the genetic manipulation of PDEδ showed identical effects on cell growth, demonstrating that PDEδ is a valid tar-get for the pharmacological therapy of KRas-dependent tumors. Second, murine pancreatic cancer cells, derived from transgenic mice, with ei-ther one (oncogene addiction) or two oncogenic mutations (synthetic sickness) were used for a synthetic lethal screen in the presence of small molecule PDEδ inhibitors. Both cell lines either express oncogenic KRas or oncogenic KRas in combination with mutant p53 under the control of endogenous promoters. Here, the cell line with the additional loss of p53 fuction seemed to be more resistant to PDEδ inhibition by Deltarasin. This work demonstrates that the availability of PDEδ is inevitable to ensure survival of oncogenic KRas-dependent cancer cells. The effects on growth in hu-man KRas-dependent cell lines and the different behaviors observed in the mu-rine systems prove that the mutation status is critical for the susceptibility to-wards PDEδ inhibition and the resulting interference with the spatial organiza-tion of KRas. The acquisition of additional oncogenic mutations allows for better adaptation to changes in the environment and ensures cellular survival.

Onkogenes KRas wird mit einer Vielzahl von Krebserkrankungen wie Bauchspeicheldrüsen-, Dickdarm- und Lungenkarzinomen assoziiert, die mit einer schlechten Prognose und Überlebenschance für den Patienten einhergehen. Durch onkogene Mutationen wird Ras in einem dauerhaft aktiven Zustand ge-halten und nachgeschaltete Signalkaskaden werden so permanent aktiviert. Die Folgen sind unkontrolliertes Wachstum und Überleben entarteter Zellen. Des-halb stellen alle Ras-Proteine interessante Angriffspunkte für zielgerichtete Krebs-Therapien dar. Trotz bekannter Struktur und Funktionen ist Ras bis heute ein „undruggable“ Protein, bei dem eine zielgerichtete Therapie sehr schwierig ist. In dieser Arbeit wurde der Krebsphänotyp in verschiedenen KRas-abhängigen Modellsystemen untersucht. Zuerst wurde in humanen Krebszelllinien, die aus verschiedenen Tumorgeweben stammten, der Phänotyp nach chemischer Inhi-bition und genetischer Herabregulation von PDEδ untersucht. Alle Zelllinien wiesen unterschiedliche Abhängigkeiten von onkogenem KRas auf, wobei ein starker Einfluss auf das Wachstum nur bei KRas-abhängigen Pankreas- und Lungenkarzinomzellen, aber nicht bei KRas-abhängigen Dickdarmkarzinomzel-len beobachtet werden konnte. Die jeweiligen Wildtyp-Zellen zeigten zumeist kein vermindertes Wachstum. Die genetische Manipulation zeigte exakt die gleichen Effekte auf das Zellwachstum wie der neue PDEδ Inhibitor Deltazino-ne 1, was bedeutet, dass PDEδ ein geeignetes Zielprotein für die gerichtete pharmakologische Therapie KRas-abhängiger Tumore ist. Als nächstes wurden zwei Zelllinien aus dem Pankreas von transgenen Mäu-sen, die entweder eine („oncogene addiciton“) oder zwei onkogene Mutationen („synthetic sickness“) tragen, für einen genetischen Screen in Gegenwart von chemischen PDEδ-Inhibitoren, verwendet. Die Zelllinien exprimieren entweder onkogenes KRas oder onkogenes KRas in Kombination mit mutiertem p53 unter endogener Promoterkontrolle. Wie zu erwarten war die Zelllinie mit der zusätzlichen p53-Mutation resistenter gegenüber dem PDEδ-Inhibitor Deltarasin. Diese Arbeit verdeutlicht, dass die Verfügbarkeit von freiem PDEδ unabdingbar für das Überleben von KRas-abhängigen Zellen ist. Die Auswirkungen der PDEδ-Inhibition auf das Zellwachstum in humanen KRas-abhängigen Zellen und die Unterschiede im Verhalten der beiden Mauszelllinien verdeutlichen, dass der Mutationsstatus einen kritischer Faktor für die Empfindlichkeit gegen-über PDEδ-Inhibitoren und der daraus resultierenden gestörten räumlichen Or-ganisation von KRas darstellt. Der Erwerb zusätzlicher onkogener Mutationen erlaubt es Zellen alternative Signalwege zu nutzen, um auf äußere Einflüsse reagieren und so ihr Überleben sichern zu können.
Keywords: Ras; KRas; PDEdelta; pancreatic cancer; colon rectal cancer; shRNA; Deltarasin; Deltazinone 1; mPDAC; p53; 570; 540